Simple microwave synthesis of TiO2/NiS2 nanocomposite and TiO2/NiS2/Cu nanocomposite as an efficient visible driven photocatalyst. Issue 11 (1st August 2019) - Mahmood, Peshawa H.; Amiri, Omid; Ahmed, Sangar S.; Hama, Jwameer Rasool
Abstract: Approximately 47% of solar-terrestrial radiation is visible. It is a great achievement to produce a highly efficient visible driven photocatalyst. Here TiO2 /NiS2 /Cu nanocomposite was prepared as a highly active visible driven photocatalyst. TiO2 /NiS2 /Cu nanocomposite was prepared by microwave method. It degrades 92%, 86%, 87%, and 88% of Rhodamine B (RhB), Methyl orange (MO), Acid Black 1 (AB1), and Acid Brown 214 (AB214), respectively. Adding NiS2 and Cu to TiO2 dramatically increased the degradation efficiency from 17% for bare TiO2 to 92% for TiO2 /NiS2 /Cu nanocomposite under visible light. As-prepared TiO2 /NiS2 /Cu nanocomposite was characterized by SEM, TEM, XRD, DRS, BET, and EDX.